TRAINING PROGRAM BY LECTURERS FOR STUDENTS ABOUT ETHICS AND SOCIAL RESPONSIBILITY IN INTERNATIONAL BUSINESS - Azhar; M.subhan; Rico Nur Ilham (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Business ethics is everything about guiding norms for a company in making decisions. Business ethics has several theoretical explanations, namely the theory of virtue, theory of rights, theory of deontology, theory of teleology. Ethics is defined as an individual's beliefs about whether certain decisions, behaviors or actions are right or wrong. Ethical behavior in cross-cultural and international contexts is how organizations treat employees, how employees treat organizations, how organizations and employees treat other economic agents. Social responsibility is a collection of organizational obligations to protect and promote the community in which the organization works. . Some organizations recognize that they have all three areas of responsibility and strive to achieve this, others emphasize only one or two areas of social responsibility. And very few do not know social responsibility at all.